Effect Of Boiling Time In Saline Solution To Reduce Cyanide Acid Levels Of Selected Indonesian Dried Bamboo Shoots - Rima Kumalasari,; Dede Zainal Arif,; Isnaini Fitrianti,; Ade Chandra Iwansyah, (Enhanced Knowledge in Sciences and Technology, 2021)
Bamboo shoots are potential materials to be used as a food source.  Cyanide acid in bamboo shoots may cause constraints in food processing. One of which can be done by a boiling process in saline solution. This study aims to examine the reduction in cyanide levels in several types of Indonesian bamboo shoots due to the effect of boiling in a salt solution. This study used a completely randomized design, two factors, 3 replications. The first factor is the variety of bamboo shoots, and the second factor is the boiling time in a salt solution. the first factor was bamboo shoots varieties, namely Betung (A1), Kuning (A2), Buluh (A3), and Gombong (A4), and the second factor was boiling time consisting of five levels: t1 = 0 minutes, t2 = 5 minutes, t3 = 10 minutes, t4 = 15 minutes, and t5 = 20 minutes. Results show that Boiling time and type of bamboo shoots had a significant effect on cyanide reduction in the dry slices of bamboo shoots. Betung variety experiencing a decrease in cyanide more than other varieties, from 426.55mg/1000g to 20.03mg/1000g (cyanide reduction = 95.30%). While the Gombong variety from 454.52 mg/1000g to 24.16mg/1000g (cyanide reduction = 94.68%), Kuning variety from 327.44mg/1000g to 21.66mg/1000g (cyanide reduction = 93.39%), and Buluh variety from 451.4mg/1000g to 42.48mg/1000g (cyanide reduction = 90.59%).